2019
DOI: 10.1055/a-0962-1283
|View full text |Cite
|
Sign up to set email alerts
|

Total and Regional Body Composition of NCAA Division I Collegiate Female Softball Athletes

Abstract: The purpose of this study was to evaluate total, regional, and throwing versus non-throwing arm body composition measures across the 4 major positions of NCAA Division I female softball players using dual X-ray absorptiometry (DXA) (n=128). Total and regional total mass (TM), fat mass (FM), lean mass (LM), bone mineral density (BMD), bone mineral content (BMC), and visceral adipose tissue were measured. Athletes were separated into: pitchers (n=32), catchers (n=13), outfielders (n=39), and infielders (n=44). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
(45 reference statements)
1
21
0
Order By: Relevance
“…Males' inter-positional VAT mass comparisons revealed centers and power forwards to have higher VAT mass than all other positions. Furthermore, the current study's females demonstrated a similar VAT mass range (57.1-290.8 g) to that recently reported [16] in female softball players (80.1-220.8 g), with centers having higher VAT mass compared to point guards and shooting guards.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Males' inter-positional VAT mass comparisons revealed centers and power forwards to have higher VAT mass than all other positions. Furthermore, the current study's females demonstrated a similar VAT mass range (57.1-290.8 g) to that recently reported [16] in female softball players (80.1-220.8 g), with centers having higher VAT mass compared to point guards and shooting guards.…”
Section: Discussionsupporting
confidence: 84%
“…The current study also compared VAT mass across male and female basketball player positions. To date, five known studies have reported VAT mass in a male athlete (football, baseball) [14,15,17] and female athlete (equestrian, softball) [13,16] population. Previously, Bosch et al [18] examined sex-specific VAT mass accumulation in healthy male and female non-athletes, reporting males' and females' VAT mass to significantly increase upon individuals reaching a BF % threshold of 23.4 % and 38.3 %, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With research reports suggesting that both decreased ROM and increased BMI are associated with an increased risk of injury, it can be theorized that an increased BMI may be exaggerating ROM deficits leading to an increased risk of injury [24]. Although there have been proposed mechanisms of injury related to higher BMI in athletes, the purpose of the current study was to examine if functional characteristics of hip and shoulder ROM were related to BMI classification.…”
Section: Introductionmentioning
confidence: 93%
“…Injury rates are already a concern among softball pitchers, as research has shown pitchers are 2.6 times more likely to be injured than positional players. Of similar concern, reports have also revealed pitchers displayed the highest body fat percentage on a collegiate softball team [24] and were the only players on NCAA Division I collegiate teams to increase body fat throughout the course of a season [25]. This highlights the need for research to determine the effects of increased BMI within pitchers, who undergo large physical demands in their pertinent role on the field, and who are regularly exposed to high pitch counts and injury [26].…”
Section: Introductionmentioning
confidence: 93%